國小教師使用教用版電子教科書之滿意度：以學校地區、資訊素養與教學環境狀況為探討因素 School Region, Teachers' Information Literacy and Teaching-Related Environmental Factors as Variables in Taiwanese Elementary School Teachers' Satisfaction in Using Teacher-Version Electronic Textbooks - 余心蓓 Shin-Pei Yu; 魏彗娟 Huei-Chuan Wei; 周倩 Chien Chou (National Taiwan Normal University, 2017)
本研究以臺灣各地區具有使用教用版電子教科書經驗之756 位國小教師為對象，以問卷調查法瞭解教師對電子教科書的整體滿意度，並探討教師的個人背景因素是否會影響此滿意度，進一步研究外在環境在教師資訊素養與使用電子教科書滿意度之間的中介效果。研究發現有：一、國小教師對於電子教科書的整體使用滿意度佳，尤其是對「教學便利性」滿意度最高。二、教師的電子教科書使用滿意度會因個人任教學校之「學校規模」、「學校地區」、「是否處於偏遠地區」而有所不同。三、國小教師的資訊素養與其電子教科書使用滿意度之間，受到教學環境狀況之「資訊設備」中介影響。最後，本研究針對上述發現，進行討論，並提出若干建議供未來研究、教師及行政人員參考。 The purpose of this survey study was to determine if Taiwanese elementary school teachers' satisfaction with teacher-version electronic textbooks differed because of demographic differences. Furthermore, the current study investigated the mediating effect of perceived environmental factors on the relationship between teachers' information literacy and satisfaction with electronic textbooks. The participants were 756 teachers at elementary schools in all areas of Taiwan. The major findings of this study were as follows: (1) In general, teachers were satisfied with the use of electronic textbooks. The dimension of "convenience" received the most favorable score. (2) "Number of school classes," "school region," and "teaching in remote/non-remote areas" had significant effects on satisfaction with electronic textbooks. (3) Environmental factors exhibited a mediating effect between teachers' information literacy and satisfaction with electronic textbooks. This study discussed the statistical results obtained and proposed suggestions and implications for teachers and future studies.